Comparative effects of desiccation, heat shock and high temperatures on seed germination of savanna and forest tree species. (21st July 2013) - Ribeiro, Leandro C.; Borghetti, Fabian
Abstract Although forest and savanna biomes predominate in tropics regions, the factors that control their distribution remain unclear. South American savannas occur in regions that are considered warm and humid enough to support forests, indicating that agents other than climate determine the occurrence of one or the other physiognomy. Herbivory, fire and water deficit have been considered environmental filters that limit the forest species encroachment in savanna physiognomies, but the effects of these filters on the capability of these species to recruit from seeds remain poorly understood. In this study we investigated how stress factors characteristic of savanna environments, such as soil desiccation, heat shocks and high temperatures affect the survival and germination of seeds from savanna and forest tree species. We found that desiccation (to 5%) reduced the germination percentage of forest seeds, but had no effect on the germination of savanna seeds. Forest seeds were less tolerant to heat shocks of 140°C and 200°C, and showed lower germination percentage at temperatures of 35 and 40°C, when compared with savanna seeds. Savanna seeds presented longer germination times and higher germination variance than forest seeds, indicating a risk‐spreading germination strategy among savanna species. The low tolerance of forest seeds to desiccation, heat shock and high temperatures may explain the low recruitment of forest trees into savanna physiognomies. Climate change models predict lower soil moisture, higher temperatures and higher fires frequency for South America biomes. Our results suggest that savanna species are likely to be more capable of withstanding the effects of these changes than forest species.